Conditions for one direction convexity and starlikeness - Mamoru Nunokawa; Oh Sang Kwon; Young Jae Sim; Ji Hyang Park; Nak Eun Cho (Journal of Inequalities and Applications, 2016)
Abstract We investigate several sufficient conditions on a function to be convex in one direction or starlike in one direction.